ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAKAN TIDAK AMAN DI PT PELINDO IV BALIKPAPAN - Liku, James Evert Adolf; Haryanto, Didik; Hasma, Aftonun Nuha (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Unsafe action is a failure to follow the requirements and correct work procedures, thereby increasing the likelihood of accidents. As many as 80%-85% of work accidents are caused by negligence or human error. The number of work accidents at PT. Pelindo IV Balikpapan is categorized as zero accident. However, the description of work behavior at PT. Pelindo IV Balikpapan is still far from the safe category. Use of tools that are not in accordance with regulations, not using appropriate PPE and other violations that can still be encountered in the daily work process. This study aims to determine whether the factors of knowledge and training can influence unsafe action on workers at PT. Pelindo IV Balikpapan. This type of research is using a quantitative approach, namely research related to scores because data collection uses a questionnaire as the main tool for collecting data. The type of research used is obserbasional which is cross sectional with primary and secondary data collection methods. The population is all workers who are in the field as many as 33 workers. The results of this study indicate that knowledge and training factors have a significant effect on unsafe action. Keywords : Training, Knowledge, PT. Pelindo IV Balikpapan, Unsafe Action